Maximizing revenues through developing a life cycle service offering for Metso’s DRI Smelting Furnace - Hoisko, Anna (My University, 2024)
In an era where manufacturing businesses increasingly recognize the value of service oriented approaches, this study investigates the shift of an industrial machinery com pany from a traditional product-centric approach to service-oriented one. By examin ing earlier research and gathering empirical data from the case, the study aims to guide the case company toward a strategic shift that emphasize aftermarket services as a way to create continuous revenue streams, foster organic growth, and long-term customer relationships throughout the equipment’s lifespan. Therefore, the thesis delves into the concept of life-cycle service offerings, adding to the body of literature on industrial services and informing the strategic decision-making of the case com pany. This study presents a case-specific framework demonstrating the life-cycle service of ferings for DRI Smelting Furnace. Beyond theoretical concepts, the framework provides practical guidelines that resonate throughout the organization, fostering a deeper un derstanding and widespread adaption. The framework is based on maintenance strate gies and operational equipment efficiency to answer problems customers may face through the equipment’s lifespan. The ultimate goal is to form a service-based business model for the technology, where physical products and life-cycle service offerings complement each other. With the help of the concepts, aspects, and service opportunities presented, this study may help managers examine, benchmark, and develop their aftermarket offerings and business models, bridging the gap between products and services. This study contributes not only to the specific context of the DRI Smelting Furnace but also to the broader dis course on how organizations can elevate their service offerings, ensuring sustained success in an ever-evolving industrial landscape.
Keywords: business models; industrial companies; service business; corporate strategies; services; product life cycle; fi=Johtaminen ja organisaatiot|en=Management and Organization|; Master’s Programme in Strategic Business Development